IMPLEMENTASI KEBIJAKAN TATA KERJA SEKRETARIAT DAERAH KABUPATEN POSO - Bagia, David (Katalogis, 2018)
This study aims to determine and analyze the Implementation of the Working Policy of the Regional Secretariat of Poso District. Measuring Policy Implementation in this study using Policy Implementation theory proposed by Edwards III (in Subarsono, 2003: 53), including: Communications, Resources, Disposition, and Bureaucracy Sturktur. This research is a descriptive type research with qualitative approach. Informants in the study were determined using purposive techniques. This research takes place at the Regional Secretariat of Poso District. Informant research in this study as many as 5 (five) people. The data were collected using Observation, Interview, and Documentation techniques. Data analysis in this study include: Data collection, Data reduction, Data Presentation, and Conclusion. The results obtained in this study indicate the Implementation of the Working Policy of the Regional Secretariat of Poso Regency has not been effective, because of 4 (four) indicators of policy implementation used as a benchmark there are still two indicators that have not run well ie the elements of Communications and Structural Elements Bureaucracy. 2 (two) other indicators namely Disposition and Resources indicate the conditions that have been effective.